Dinâmica de uso e ocupação em paisagens costeiras no Município de Icapuí-Ce - Moretz-Sohn, Clarissa Dantas (2018)
Management of the coastal zone is generally challenging due to the dynamics of marine and coastal ecosystems. The high level of complexity are finding both in the physical parameters as in the questions and interests of the users. A participatory methodology was used to search for an integrated analysis on the use and occupation in the beaches of Retiro Grande and Ponta Grossa, located in the western section of Icapuí. So, through interviews, social cartography workshops and geoprocessing tools became possible to understand the processes of changes in the coastal landscapes of the region. The beaches of Retiro Grande and Ponta Grossa, are knew by high historical, cultural, environmental and scenic value. There are vestiges of ancient uses and occupations in this region (about 4 thousand years ago) as well as the indigenous tribes Jabarana, Caiçara and Tremembés. In addition, artifacts from European vessels from the colonization period were found which correspond to favorable geographical conditions in the region. The local communities are traditionally linked to artisanal fishing and subsistence agriculture. However, the forms of use and occupation have changed over time due to geoenvironmental and climatic processes, infrastructure development and socioeconomic aspects. Thus, society and nature compose as landscapes in a dialectical and dynamic way, being necessary to know a history of places and processes of transformation of space for analysis the use and occupation of land and and the changes in landscapes.